Metal‐Bonded Redox‐Active Triarylamines and Their Interactions: Synthesis, Structure, and Redox Properties of Paddle‐Wheel Copper Complexes. Issue 3 (14th January 2019) - Akintola, Oluseun; Böhme, Michael; Rudolph, Manfred; Buchholz, Axel; Görls, Helmar; Plass, Winfried
Abstract: Four new triphenylamine ligands with different substituents in the para position and their corresponding copper(II) complexes are reported. This study includes their structural, spectroscopic, magnetic, and electrochemical properties. The complexes possess a dinuclear copper(II) paddle‐wheel core, a building unit that is also common in metal‐organic frameworks. Electrochemical measurements demonstrate that the triphenylamine ligands and the corresponding complexes are susceptible to oxidation, resulting in the formation of stable radical cations. The square‐wave voltammograms observed for the complexes are similar to those of the ligands, except for a slight shift in potential. Square‐wave voltammetry data show that, in the complexes, these oxidations can be described as individual one‐electron processes centered on the coordinated ligands. Spectroelectrochemistry reveals that, during the oxidation of the complexes, no difference can be detected for the spectra of successively oxidized species. For the absorption bands of the oxidized species of the ligands and complexes, only a slight shift is observed. ESR spectra for the chemically oxidized complexes indicate ligand‐centered radicals. The copper ions of the paddle‐wheel core are strongly antiferromagnetic coupled. DFT calculations for the fully oxidized complexes indicate a very weak ferromagnetic coupling between the copper ions and the ligand radicals, whereas a very weak antiferromagnetic coupling is found among the ligand radicals. Abstract : Spinning the wheel : Triphenylamine ligands at a copper paddle‐wheel core are studied as models for the properties of such building units in polymeric structures with particular emphasis on the electronic structure upon oxidation of the triphenylamine ligand framework. The interaction of the oxidized radical species of the triphenylamine ligands in these complexes is investigated by using electrochemical, spectroelectrochemical, and computational methods.